A rare and interesting case of heterotopic cervical pregnancy after intracytoplasmic sperm injection and embryo transfer - Ritu Punhani; Kundavi Shankar; Thankam R Varma (Wolters Kluwer Medknow Publications, 2016)
The wide use of assisted reproductive technologies has contributed to the increased risk of ectopic and subsequently heterotopic pregnancy (HP) rate. Cervical ectopic pregnancy is a very rare and life-threatening form of ectopic pregnancy that can also present as HP. We are describing here a case of 34-year-old woman who presented with bleeding heterotopic cervical pregnancy (HCP). The concomitant viable cervical and intrauterine pregnancies were diagnosed at 8 weeks of gestation. Selective fetal reduction was done for cervical pregnancy following which uterine artery embolization was done as a life-saving measure, and subsequently, injection methotrexate was also given. Although cervical component of HCP has the potential for high morbidity due to massive hemorrhage, the mortality rate is low due to early ultrasonographic diagnosis. A high index of suspicion is mandatory for early diagnosis.